High-Performance Carbon Nanotube Electronic Devices: Progress and Challenges - Zirui Zhang; Nie Zhang; Zhiyong Zhang (Micromachines)
As silicon-based complementary metal-oxide-semiconductor (CMOS) technology approaches its physical and scaling limits at sub-3-nanometer nodes, critical challenges including the short-channel effect (SCE), surging power consumption, and aggravated parasitic effects have severely constrained further improvements in device performance, integration density, and energy efficiency. Carbon nanotubes (CNTs), with their superior electrical properties, exceptional gate controllability enabled by one-dimensional nanostructure, and compatibility with existing semiconductor processes, have emerged as an ideal candidate material for post-silicon high-performance electronics. Since their discovery, CNT electronics have evolved from fundamental research to a comprehensive technological framework. This review first systematically elaborates the physical characteristics of CNTs and operation mechanisms of electronic devices. Subsequently, we comprehensively summarize recent research progress in high-performance CNT electronic devices with particular emphasis on their breakthrough achievements. Through critical analysis of current developments, we thoroughly discuss fundamental challenges in material synthesis, device fabrication, and circuit integration, while evaluating potential solutions. Finally, we concentrate on future development directions for high-performance CNT devices, aiming to call for collaborative efforts from both academia and industry to accelerate the transition of CNT electronics from laboratory research to industrial implementation.